A new stonefly from Lebanon, Perlodes thomasi sp. n. (Plecoptera: Perlodidae) - Vinçon, Gilles (Illiesia, 2013)
A new Perlodes species from Lebanon, Perlodes thomasi, is described and compared with its closely related species P. floridus floridus Kovács & Vinçon2012 from the Balkan Peninsula and P. floridus peloponnesiacus Kovács & Vinçon 2012 from the Greek Peloponnes. These taxa differ from all the previously described Perlodes species primarily in the exceptional shape of the egg and the attachment disc. P. thomasi sp. n. is a cold stenothermal species occurring in the close surrounding of rheocrene karstic springs on theWestern slope of Mount Lebanon. The list of the 16 stoneflies known from Lebanon so far is updated and discussed.
Keywords: entomology; Perlodidae; Plecoptera; Lebanon; new species